New normal: Is the village ready? (a webinar on preparing villages for the new era) - Hendrikus Hironimus Botha; Makarius Erwin Bria; Yohanes Fritantus; Pionisius Minggu; Yoakim Rembu; Yohanes Imanuel Naif (Universitas Muhammadiyah Magelang, 2023)
This community service activity aims to examine the extent of village preparation in facing the implementation of the New Normal policy (new normal life) and at the same time to provide information through socialization related to the implementation of the New Normal policy. The village as the spearhead in implementing the New Normal policy should prepare all resources that can support the implementation of the policy. This New Normal policy is designed to support the economic life of the people who had experienced a decline during the Covid-19 prevention and handling period. The purpose of this policy is to re-increase the productivity of the people who had stopped while keeping them safe from Covid-19. Forms of Community Service Webinar through online media (Google Meet). The results of the service activities carried out were that the people of Oeprigi Village and Kaenbaun Village, which were the target group in this activity, knew and understood the New Normal policy.